Digital transformation and value chains: Introduction - Florian Butollo; Gary Gereffi; Chun Yang; Martin Krzywdzinski (Global Networks, 2022)
New digital technologies based on the internet of things and artificial intelligence play centre stage in contemporary discussions about the prospects for economic development and the future of work. This article summarizes theoretical and empirical contributions on how these technologies affect global value chains (GVCs). We argue that the leading paradigms that analyse global production – the GVC framework and the related global production networks (GPNs) approach – are in need of some `technological uprading' themselves. The GVC/GPN approaches acknowledge that technology is constitutive for the emergence of geographically fragmented production, but rarely address directly how technological change affects interfirm relations. The authors provide a framework that acknowledges the key role of technology while situating digital tools and systems in their social embeddedness, that is the role of human agency and institutions in shaping their development and impact. A research agenda is outlined focusing on three topics: the varieties of digitalization approaches in different world regions, the role of data as a specific form of intangible resource and the role of platform business models for industrial ecosystems. These topics are addressed in the special issue of Global Networks on `Digitalization and Value Chains' introduced by this contribution.
Keywords: 330; global commodity/value chains; global production networks; globalization; governance; ICT; transnational social relations